Concepts of Research Methods and Statistics Used in Program Evaluation - Raluca Antonie (GÂRBOAN) (Transylvanian Review of Administrative Sciences, 2009)
This paper introduces aspects related tothe relation between Evaluation on the oneside and Research methods and Statistics onthe other side. Because of the interdisciplinaryprofile of program evaluation as a theoreticaland practical field, sometimes the importanceof using the appropriate research methods andthe adequate statistical methods is regarded ashaving a secondary importance. Based on our ownobservations and on some other assessments, weare able to state that the use of research methodsand of statistical methods should be at the core of program evaluation.